La cooperación para el desarrollo tras la Intifada: nuevas prioridades ante un futuro incierto - Álvarez-Ossorio Alvariño, Ignacio (Revista Española de Desarrollo y Cooperación, 2023)
The beginning of the Peace Process with the Oslo Agreement in 1993 had created great expectations faced with the possibility of resolving on a pacific way the Israel-Palestinian conflict. Ten years later there is a generalized pessimism about the future. The return to the dynamics of violence with the Intifada in 2000 and the collapse of negotiations after the fail of Taba round in 2001, forced to change the priorities of international development cooperation towards the Palestinian Territories and, in particular, European and Spanish cooperation. Therefore, if the cooperation efforts committed by the donor community in the nineties were directed to support the creation of a Palestinian proto-state infrastructure, from 2000 these efforts have been mainly devoted to take care of the most basic needs of the Palestinian population, through food security and complex emergency projects. As a World Bank Report as put it: “Long term investment has been sacrificed by short term survival”.